Estrategias competitivas para el fortalecimiento de las pymes del sector molinero del cantón Latacunga - Caso cereales la Pradera. - Espín Bedón, Karen Estefanía (2021)
The objective of the research work was to design competitive strategies to strengthen the marketing of the products of the company "Cereales La Pradera". Due to the high number of competitors that currently exist in the market, the company level of sales has been significantly affected in recent years. The research covers as a first part and under a qualitative approach the theoretical foundation related to the topics to be discussed in the analysis of external and internal factors that affect the organization and research that is done through the implementation of tools for strategic diagnosis. The evaluation matrices of Internal and External Factors identified the weaknesses and threats that are affecting the organization and allowed corrective measures to be implemented, taking advantage of the strengths and opportunities of the company, which were synthesized in a FODA Matrix. The application of the PEYEA Matrix and Grand Strategy Matrix was also carried out, which determined that “Cereales La Pradera” is in the "Conservative Quadrant" and with a "Soft Competitive Position". In other words, the organization does not take too many risks and remains close to its basic capabilities. Therefore, it is necessary to carry out development and integration strategies in order to be competitive in the market and therefore increase its profitability. Under a quantitative methodology, descriptive field research was carried out in order to identify the tastes and preferences of potential customers of “Cereales La Pradera's” products and other geographic and demographic variables that were used as guides for the design of competitive strategies and for the development of a cluster analysis that allowed market segmentation.